Frontal lobe growth is impaired in fetuses with congenital heart disease. (13th April 2021) - Paladini, D.; Finarelli, A.; Donarini, G.; Parodi, S.; Lombardo, V.; Tuo, G.; Birnbaum, R.
ABSTRACT: Objectives: The primary objective of this study was to assess whether fetuses with congenital heart disease (CHD) have smaller frontal brain areas compared with normal controls. The secondary objective was to evaluate whether there are any differences in frontal brain area between cases with different types of CHD, grouped according to their impact on hemodynamics. Methods: This was a retrospective cross‐sectional study, including 421 normal fetuses and 101 fetuses with isolated CHD evaluated between 20 and 39 gestational weeks at our fetal medicine and surgery unit in the period January 2016–December 2019. The study group was subdivided, according to the CHD hemodynamics, as follows: (1) hypoplastic left heart syndrome and other forms of functionally univentricular heart defect; (2) transposition of the great arteries; (3) conotruncal defects and other CHDs with large shunts; (4) right ventricular outflow tract obstruction, without a hypoplastic right ventricle; (5) left outflow tract obstruction; (6) others. The transventricular axial view of the fetal head was used as the reference view, on which the frontal lobe anteroposterior diameter (FAPD) and the occipitofrontal diameter (OFD) were measured, assuming the former to be representative of the area of the frontal lobes. The FAPD/OFD ratio was then calculated as FAPD/OFD × 100. These two variables (FAPD and FAPD/OFD ratio) were then evaluated and compared between the study and control groups. Adjustment for gestational age, both via multiple linear regression and by using a‐posteriori matching based on the propensity score, was employed. Results: In normal fetuses, FAPD showed a linear positive correlation with gestational age. In fetuses with CHD, the FAPD was shorter than in normal fetuses from the 20 th gestational week onwards, with the difference increasing after 30 gestational weeks. FAPD/OFD ratio was significantly smaller in fetuses with CHD than in normal fetuses ( P < 0.0001) at all gestational ages, with no apparent differences among the various CHD categories, all of which had smaller FAPD/OFD ratio compared with controls. Conclusions: Fetuses with CHD have a shorter FAPD and a smaller FAPD/OFD ratio compared with normal fetuses. This impaired growth of the frontal area of the brain seems to occur in all types of CHD, regardless of their impact on hemodynamics. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.